1998
DOI: 10.1128/jcm.36.8.2322-2325.1998
|View full text |Cite
|
Sign up to set email alerts
|

Isolation ofPorphyromonas gingivalisand Detection of Immunoglobulin A Specific to Fimbrial Antigen in Gingival Crevicular Fluid

Abstract: The present study evaluated the prevalence of Porphyromonas gingivalis and the correlation between the bacterial culture method and the detection of immunoglobulin A (IgA) specific to theP. gingivalis fimbrial antigen in gingival crevicular fluid (GCF). P. gingivalis was isolated from 78.3% of subgingival plaque samples obtained from active sites and 34.7% of those from inactive sites of periodontal patients. P. gingivalis was isolated from only 4.7% of healthy subjects (control group). Immunoglobulins specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…FcaRI-bearing neutrophils were predominantly located adjacent to the deeper part of the periodontal pocket where large numbers of microorganisms reside. This indicates that FcaRI-mediated phagocytosis of IgA-opsonized antigens is likely to aid in elimination of penetrating bacteria, because (1) about 10%-30% of the plasma cells in periodontal lesions produce IgA (Okada et al 1983, Takahashi et al 1997, Myint et al 1999), (2) IgA antibodies specific for potential periodontal pathogens are found in serum and gingival fluid from patients with CMP (Tolo & Schenck 1985, Condorelli et al 1998, Landry 1995, and (3) we observed considerable numbers of subgingival plaque bacteria coated with IgA (present study). FcaRI on neutrophils has a higher affinity for IgA than FcgRs on the same cells have for IgG, and IgA-mediated phagocytosis in the tissue may therefore be more effective than that mediated by IgG (Mazengera & Kerr 1990, Stewart et al 1994, Raghavan & Bjorkman 1996.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…FcaRI-bearing neutrophils were predominantly located adjacent to the deeper part of the periodontal pocket where large numbers of microorganisms reside. This indicates that FcaRI-mediated phagocytosis of IgA-opsonized antigens is likely to aid in elimination of penetrating bacteria, because (1) about 10%-30% of the plasma cells in periodontal lesions produce IgA (Okada et al 1983, Takahashi et al 1997, Myint et al 1999), (2) IgA antibodies specific for potential periodontal pathogens are found in serum and gingival fluid from patients with CMP (Tolo & Schenck 1985, Condorelli et al 1998, Landry 1995, and (3) we observed considerable numbers of subgingival plaque bacteria coated with IgA (present study). FcaRI on neutrophils has a higher affinity for IgA than FcgRs on the same cells have for IgG, and IgA-mediated phagocytosis in the tissue may therefore be more effective than that mediated by IgG (Mazengera & Kerr 1990, Stewart et al 1994, Raghavan & Bjorkman 1996.…”
Section: Discussionsupporting
confidence: 55%
“…Large numbers of plasma cells, mainly producing IgG and IgA, are present in the inflammatory cell infiltrate formed beneath the dental pocket epithelium (Okada et al 1983, Takahashi et al 1997. Increased levels of IgG and IgA reactive with bacteria in dental plaque are found in both serum and gingival fluid from patients with CMP as compared to persons with clinically healthy gingiva (Tolo & Schenck 1985, Condorelli et al 1998. The variable parts of immunoglobulin molecules bind antigen, whereas the constant regions mediate biological activities.…”
Section: Chronic Marginal Periodontitis (Cmp)mentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies have focused on the comparison of clinically different sites, 28,30,31 of serum and oral antibody levels, 26,32,33 or on the relationship between specific antibodies and bacteria collected from the same site. 13,34 Studies in periodontally healthy subjects are scarce, usually involve small series of subjects, and in most cases report on the absence of bacteria and low or absent specific IgG levels.…”
Section: Discussionmentioning
confidence: 99%
“…In saliva, secretory IgA constitutes the main specific immune defense mechanism and may play an important role in the homeostasis of oral microorganisms (19). Detection of IgA antibodies specific to Porphyromonas gingivalis in gingival crevicular fluid could be utilized as a predictive parameter of periodontal infection (20). Neutrophil elastase, which was derived from the effector system of acute inflammatory response, was also identified in gingival crevicular fluid of patients with periodontal disease (21).…”
Section: Discussionmentioning
confidence: 99%